Laparoscopic implantation of neuromodulators for treating urinary dysfunctions and improving locomotion in multiple sclerosis patients. Issue 12 (December 2015) - Lemos, Nucelio; Bichuetti, Denis; Marques, Renato; Conde, Maria; Oliveira, Acary; Girão, Manoel
Abstract Introduction and hypothesis The laparoscopic implantation of neuromodulation electrodes—the LION procedure—was first described as a rescue procedure in patients with local complications of a Brindley procedure. The objective of this video article is to demonstrate the technique for the laparoscopic implantation of electrodes for bilateral neuromodulation of femoral, sciatic and pudendal nerves and describe our initial experience with two multiple sclerosis (MS) patients. Method This is a retrospective analysis of two patients with MS and neurogenic detrusor overactivity. A quadripolar electrode was implanted with two poles into the Alcock's canal and the two other laying over the lumbosacral trunk. The other two electrodes were implanted posteriorly to the femoral nerves. Results At the neuromodulation trial, both patients presented a full recovery of urinary symptoms. One of them found it easier to stand up for transfers and daily activities and the other managed to advance from the wheelchair to the walker and both patients received the permanent implant. At 1-year follow up, urinary results were maintained and 1 patient presented a disease relapse, demanding multiple reprogramming sessions. Conclusion Our initial observations are encouraging and indicate that the LION procedure seems to produce in MS patients similar results to those observed in patients with spinal cord injury. Patients, however, should be advised that MS is a progressive disease and that the positive effects of neuromodulation can potentially fade with time and that multiple reprogramming sessions might be necessary.